2007
DOI: 10.1007/s11627-007-9039-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct somatic embryogenesis from cotyledon and cotyledonary node explants in bishop’s weed Trachyspermum ammi (L.) sprague

Abstract: A three-stage procedure for embryogenesis in Trachyspermum ammi was developed from cotyledon and cotyledonary node explants cultured in Murashige and Skoog (MS) liquid medium supplemented with 0.2 mg l −1 2,4-dichlorophenoxyacetic acid (2,4-D). Globular somatic embryos without intervening callus phase developed in 4 wk. The development of embryos to heart and torpedo stages required second-stage subculture of the explants (along with developing embryos) in liquid medium with lower concentrations of 2,4-D. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Proline has been proven to have a positive influence on embryogenic callus formation in Iris (Jéhan et al, 1994;Kereša et al, 2009), whereas CH has induced somatic embryos from root explants in carrots (Smith et al, 1997). Purohit and Kothari (2007) reported that subculturing bishop"s weed somatic embryos in MS medium supplemented with 100 mg/L of CH significantly promoted the maturation of heart and torpedo stage to cotyledonary stage somatic embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Proline has been proven to have a positive influence on embryogenic callus formation in Iris (Jéhan et al, 1994;Kereša et al, 2009), whereas CH has induced somatic embryos from root explants in carrots (Smith et al, 1997). Purohit and Kothari (2007) reported that subculturing bishop"s weed somatic embryos in MS medium supplemented with 100 mg/L of CH significantly promoted the maturation of heart and torpedo stage to cotyledonary stage somatic embryos.…”
Section: Resultsmentioning
confidence: 99%
“…e.g. plant regeneration from callus of T. ammi (Jasrai et al 1992, Sehgal andAbbas 1994), callus induction and regeneration from apical bud of Carum copticum L. (Salehi et al 2014), direct shoot micropropagation system in T. ammi by using seed as explants (Koca and Aasim 2015), direct somatic embryogenesis from cotyledon and cotyledonary node explants in T. ammi (Purohit and Kothari 2007).…”
Section: Resultsmentioning
confidence: 99%
“…SE is already known as the most appropriate regeneration system based on the exceptional totipotency of pro-embryonic masses (PEMs) giving rise to hundred of somatic embryos able to regenerate into plants. Several explants have been used to induce PEMs including immature flower tissues [7], anthers [7,8], ovaries [7,9], microspores [10], mature and immature zygotic embryos [9,11], cotyledons [12,13], hypocotyls [13], petioles [14], root tip [15,16], shoot apex [17] and leaf explants [16,18]. Somatic embryos developed over the surface of embryogenic callus (indirect SE) or occasionally, directly from explants without intervening calls phase (direct SE).…”
Section: Embryogenic Cell Suspension Platform : Implementation and Relevancementioning
confidence: 99%